Analisis Pengembangan Kawasan Wisata Dosoen Kakao Di Kecamatan Glenmore Kabupaten Banyuwangi - Relis Hernanda; Riniati Riniati; Teguh Hadi Priyono (UPT Penerbitan Universitas Jember, 2020)
Dimensions of ecologial (environmental), economic, social, legal and regulatory dimensions, institutions and infrastructure and technology are important indicators in the sustainability and development of the Dosoen Kakao tourism area in the future. This study aims to determine and analyze the ecological, economic, social, legal and regulatory dimensions, institutions as well as infrastructure and technology in influencing the development of the Dosoen Kakao tourist area in Jember Regency. The data analysis method used in this study is multidimensional scaling (MDS) with several running data, namely Run Rap-Dosoen Kakao, Run Leverage, and Run Montle Carlo, to determine the condition of sustainability and the effect of sensitive attributes of each dimension. The results of the analysis show that the dimensions that influence the development of the Dosoen Kakao tourist area in Jember Regency are the ecological, economic, social, legal and regulatory, institutional, and infrastructure and technology dimensions. The sustainability status of the ecological dimension is sustainable, economic is sustainable, social is sustainable, laws and regulations are quite sustainable, institutions are quite sustainable, and infrastructure and technology are quite sustainable.